IMPLEMENTASI MULTIMEDIA INTERAKTIF 3D SEBAGAI MEDIA TERAPI VISUAL PADA ANAK PENDERITA AUTIS - Swara, Ganda Yoga; Putra, Eko Kurniawanto; Anisya, Anisya; Mandarani, Putri (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2024)
This research highlights the implementation challenges of visual therapy at Mitra Ananda Autism School, which currently relies on conventional methods using books and blocks, often leading to boredom among autistic children. Therefore, the aim of the study is to design a 3D Interactive Multimedia solution based on Android to address this issue while maintaining teacher supervision. The research methodology involves utilizing 3D multimedia technology to create an application that presents visual therapy materials in a more engaging and interactive manner. Evaluation by teachers and media experts indicates that the designed multimedia is deemed highly suitable, with assessment scores reaching 87% from teachers and 87.77% from media experts. The research has successfully developed an effective solution that addresses the monotony experienced by autistic children during visual therapy by incorporating interactive 3D multimedia technology as a highly feasible and diverse supporting medium. This solution is expected to enhance the effectiveness of visual therapy and support the development of children with autism.